2013
DOI: 10.4018/978-1-4666-4086-3.ch010
|View full text |Cite
|
Sign up to set email alerts
|

PhET Interactive Simulations

Abstract: This chapter focuses on the design and use of interactive simulations as a powerful tool for learning mathematics. Since 2002, the PhET Interactive Simulations project at the University of Colorado Boulder (http://phet.colorado.edu) has been developing and studying the use of interactive simulations in teaching and learning STEM. While the project’s initial work focused on science learning, the project now includes a significant effort in mathematics learning. In this chapter, the authors describe the PhET pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
1
3
0
1
Order By: Relevance
“…In addition, this study supports Govindarajan and Choo's (2022) ndings, which indicated that learners' attitudes regarding fractions improved due to the number line. Also, Hensberry et al (2015) support that learners' attitudes toward learning fractions with the number line were overwhelmingly positive, and these ndings were supported by the experimental group attitude during the questionnaire. Barbieri et al (2020) concur that using the number line approach increases learners' attention and attitude since it allows more discussion and strategies.…”
Section: Research Questionsupporting
confidence: 53%
“…In addition, this study supports Govindarajan and Choo's (2022) ndings, which indicated that learners' attitudes regarding fractions improved due to the number line. Also, Hensberry et al (2015) support that learners' attitudes toward learning fractions with the number line were overwhelmingly positive, and these ndings were supported by the experimental group attitude during the questionnaire. Barbieri et al (2020) concur that using the number line approach increases learners' attention and attitude since it allows more discussion and strategies.…”
Section: Research Questionsupporting
confidence: 53%
“…The majority of the lectures offered by engineering departments in higher education institutions are based on content-heavy teaching although some departments offer a number hands-on trainings that are physically carried out in the laboratories. The education division of the Royal Society of Chemistry contains a large library of exercises (PhET interactive simulations) and teaching support (Chamberlain et al, 2020). Furthermore, augmented reality based teaching can be utilized through Microsoft HoloLens technology (Brechtelsbauer, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This was an online exercise that familiarizes the students with UV-Vis spectrophotometers and data processing. A simulated spectrophotometer (PhET, University of Colorado Boulder) was be utilized to generate UV-Vis data (Figure 1) (Lancaster et al, 2013, Moore et al, 2014, Chamberlain et al, 2020.…”
Section: Part Ii: Peer Learning: Online Spectrophotometer Simulatormentioning
confidence: 99%
“…Siswa akan berlatih membentuk gambar yang menunjukkan bagian pecahan yang sesuai bilangan di sebelah kanan. Game fractions simulations ini terbukti dapat meningkatkan hasil belajar siswa secara signifikan pada materi konsep pecahan sederhana (Hensberry et al, 2015). Namun temuan yang didapatkan peneliti bahwa masih terdapat 1 dari 6 siswa yang belum memahami konsep pecahan sederhana meski telah belajar dengan aplikasi topmarks, adalah dipengaruhi oleh berbagai hal.…”
Section: Gambar 7 Tampilan Game Build a Fractions Pada Aplikasi Topmarksunclassified